The influence of perception towards social media factors on UPM students’ purchase behaviour - Liew, Soo Wei; Osman, Syuhaily (HRMARS, 2024)
The main purpose of this research was to examine the relationship between the perception towards social media factors (advertising, reviews, and influencer recommendations) and to determine the most dominant factor influencing consumer purchase behaviour. Using a simple random sampling method, 312 students from Universiti Putra Malaysia participated in this research. The data were collected from the survey done through email. The nominal scale was used in the questionnaire to gather data on respondents’ backgrounds; while the Likert scale was used for the items in consumer purchase behaviour, the perception towards social media advertising, reviews, and influencer recommendations. The result from Pearson correlation analysis shows that there were significant relationships between the perception towards social media advertising (r=0.629; p=0.000), reviews (r=0.543; p=0.000), and influencer recommendations (r=0.487; p=0.000) and students’ purchase behavior. In addition, multiple regression analysis showed that the perception towards social media advertising and reviews were the contributing predictors influencing the students’ purchases with the perception towards social media advertising as the most dominant factor (β=0.463; p=0.000). The findings imply that businesses should use social media especially social media advertising in promoting their businesses, whereas consumers should carefully consider advertising, reviews, and influencer recommendations from social media before purchasing